Flexible nonlinear periodization in a beginner college weight training class - McNamara, J. M.; Stearne, D. J. (The Journal of Strength and Conditioning Research, 2010)
The purpose of this study was to determine the effect of a flexible nonlinear (FNL) periodized weight training program compared to a nonlinear (NL) periodized weight training program on strength and power. Sixteen beginner weight training students were randomly assigned to an FNL group (n = 8) or an NL group (n = 8). The exercise program included a combination of machines and free weights completed in 30 minutes, twice per week, for 12 consecutive weeks. Both groups were assigned the same total training volume of 3,680 repetitions and the same total training repetition maximum assignments of 10, 15, and 20. The FNL group, however, was allowed to choose which day they completed the 10, 15, or 20 repetition workout. This was the only difference between the groups. Pre- and post-test measures included chest press, leg press, and standing long jump. The FNL group significantly improved by an average increase of 62 kg (p < 0.05), whereas the NL group only increased by an average of 16 kg in the leg press. The FNL group did not significantly differ in chest press or standing long jump performance when compared to the NL group. The conclusion from this study is that an FNL periodization program may be a highly effective method of training for improving leg strength. Coaches can immediately implement an FNL program by evaluating the readiness of an athlete immediately before his or her training session, then adjusting the assigned exercise intensity accordingly.